2017
DOI: 10.18203/2319-2003.ijbcp20172740
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibility pattern of urine culture isolates in a tertiary care hospital of Jharkhand, India

Abstract: Background: Urinary tract infection (UTI) is one of the common infections encountered by the clinicians. Though a good number of antimicrobial agents are available, still UTIs have become difficult to treat due to development of resistance by the uropathogens. So, regional data regarding the common uropathogens and their sensitivity pattern is required to guide the clinicians to start empirical therapy while managing UTIs. The purpose of the study was to identify different species of microorganisms, along with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 18 publications
2
13
0
Order By: Relevance
“…They were highly resistant to aminoglycosides, macrolides and fluoroquinolones as also reported by Hasan AS et al 22 Vancomycin resistance was reported in 14.5% of isolates as compared to 1.82% reported by Sood S et al 20 5.1% of Staphylococcus aureus exhibited resistance to linezolid compared to the 9.1% reported by Hasan AS et al 22 Vancomycin resistance was shown by 43.6% of Staphylococcus aureus isolates similar to the study by Kumar A et al (43.87%). 21 In our study, imipenem resistance was reported in 28.2% of Enterococcus spp. and 2.6% of Staphylococcus aureus in contrast to 8.2% and 14% reported by Somashekara SC et al respectively.…”
Section: Discussionsupporting
confidence: 46%
See 3 more Smart Citations
“…They were highly resistant to aminoglycosides, macrolides and fluoroquinolones as also reported by Hasan AS et al 22 Vancomycin resistance was reported in 14.5% of isolates as compared to 1.82% reported by Sood S et al 20 5.1% of Staphylococcus aureus exhibited resistance to linezolid compared to the 9.1% reported by Hasan AS et al 22 Vancomycin resistance was shown by 43.6% of Staphylococcus aureus isolates similar to the study by Kumar A et al (43.87%). 21 In our study, imipenem resistance was reported in 28.2% of Enterococcus spp. and 2.6% of Staphylococcus aureus in contrast to 8.2% and 14% reported by Somashekara SC et al respectively.…”
Section: Discussionsupporting
confidence: 46%
“…This was similar to the findings by Sood S et al, who reported UTI from 37.67% males and 62.42% females. 20 Female preponderance was reported from various studies: 57.74% by Kumar A et al, 70.5% by Hasan AS et al and 39.9% females compared to 9.1% males by Semwal AC et al 21,22,23 However, Patil S et al reported a slight male preponderance (57%). 24 The female preponderance is probably related to the short length of the female urethra and its proximity to the anal opening facilitating entry of bacteria into the urinary tract easily.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Urinary tract infections (UTI) are defined by the presence of a growth of more than 10 5 colony forming units (CFU) of bacteria per ml of urine for asymptomatic individual and ~10 3 CFU/ml for symptomatic individual [1,2]. In urine samples obtained by supra pubic aspiration or catheterization and in samples from a patient with an indwelling catheter, colony count of 10 2 -10 4 CFU/ml generally signifies urinary tract infection [1]. UTI are one of the commonest clinical conditions encountered by physicians and accounts for 1-6% of all medical visits [3].…”
Section: Introductionmentioning
confidence: 99%